Anotaciones a la anatomía comparada de las Umbelíferas - Rodríguez C., Rafael L. (Revista de Biología Tropical, 1957)
Descriptions and measurements of the secondary xylem components of four herbaceous Umbelliferae are presented (Table 1), as an addition to a comparative study concurrently in print, comprising 36 Umbelliferae and 38 Araliaceae (27). If the species here considered are integrated into the foregoing series, Daucus Carota is shown to have highly advanced characteristics, in harmony with its systematic position and morphologic characteristics. Arracada xanthorhiza, a South American perennial herb whose rootstock . puts out fleshy lateral growths which constitute the edible "arracacha", appears to be moderately advanced, slightly ahead of its more shrubby congeners. Faeniculum vulgare, a perennial herbaceous species, is comparable to other Apioid species of like habit such as Conium maculatum, and occupies an intermediate position in the family. Sanicula crassicaulis, a western North American herbaceous species, appears also to be well advanced, stressing the independent progress which has taken place within each sub-family. A frequent modification of scalariform lateral-wall pitting, resulting in the formation of whorled patterns is described in vessel elements of Arracacia xanthorhiza and Daucus Carota. Similar patterns have been observed in Arracada Wigginsii, Bupleurum longiradiatum, Sanicula deserticola and Pteryxia petraea. Formation of such patterns might be interpreted as a result of the reduction of vessel-element length leading to cell-wall formation as in isodiametric cells; or else, it may be an advanced modification of scalariform pitting, perhaps related to whorled patterns of "tertiary" thickening of lateral walls, reported in Heteromorpha arborescens, Heteromorpha trifoliata, Bupleurum fruticosum and also in Astrotrichia pterocarpa (araliacae). If this is the case, the whorled patterns of pitting might stand, with relation to typical scalariform pitting, as the whorled patterns of "tertiary" thickening to the simpler helicoid patterns common in Bupleurum fruticosum and in Heteromorpha, in Araliacae such as Nothopanax arboreus and Nothopanax Colensoi, as well as in Garrya Veatchii and G. Wrightii.